BENTUK PENYAJIAN TARI MANDULANG AMEH DALAM UPACARA PENYAMBUTAN TAMU DI KANAGARIAN PALANGKI KECAMATAN IV NAGARI KABUPATEN SIJUNJUNG - Fara Tiurma Andrina; Herlinda Mansyur; Susmiarti Susmiarti (FBS Universitas Negeri Padang, 2012)
This research uses qualitative research (1) aims to describe the form of Representation of Mandulang Ameh Dance in Kanagarian Palangki IV District Villages Sijunjung District. (2) The method used is descriptive analysis which the techniques to collect the data are: interviews, direct recording, literature, observation, transcription. (3) The result of this research obtained the form of Representation of Mandulang Ameh Dance that starting from preparation day before the event, such as fittings and rehearsal event in the building. The day of event in the building before the appearance there are the preparations are: put on make up the face and dress dancer, dance ready to be displayed to the dance. . Mandulang Ameh in there Hour Ceremony dance moves ranging from berhela – hela manunggu masin (bersantai – santai menungu mesin),sambah(sembah), mancaliak hari (melihat hari), manjampuik urang rumah(pulang menjemput orang rumah),pai katambang (pergi ketambang), maambiak kasiak(mengambil pasir), manggali kasiak (menggali pasir), mamisah ameh jo kasiak(memisahkan emas dan pasir), mambarasiahan ameh (membersihkan emas),mancaliak ameh(melihat emas),basanang dapek ameh(bersenang dapat emas),mangumpuan ameh(mengumpulkan emas),manuai (menuai),pesta dan pulang. Dance Mandulang Ameh in Welcoming Ceremony serves as entertainment as guests and arts events in the day - a great day. Ameh Mandulang dance danced by eight dancers with three male dancers - male and five female dancers, the costumes are simple dancers wearing traditional Minangkabau. Ameh Mandulang dance floor wearing a simple pattern such as triangles, straight lines are also circular, instrument used is talempong and Tambua also a pendendang and Tambua also a pendendang and can be displayed in the halls and open field.Key Word : bentuk penyajian, mandulang ameh, palangki,sijunjung